Molecularly Imprinted Polymer/Metal Organic Framework Based Chemical Sensors - Zhenzhong Guo (Coatings, 2016)
The present review describes recent advances in the concept of molecular imprinting using metal organic frameworks (MOF) for development of chemical sensors. Two main strategies regarding the fabrication, performance and applications of recent sensors based on molecularly imprinted polymers associated with MOF are presented: molecularly imprinted MOF films and molecularly imprinted core-shell nanoparticles using MOF as core. The associated transduction modes are also discussed. A brief conclusion and future expectations are described herein.